Zamanmekansal Deneyim Olarak Kamusal Alan - Karababa, Avşar (Fen Bilimleri Enstitüsü, 2009)
Kapitalist güçlerin bireylerin kamusal alanlarını ve özel alanlarını tehtid ettiği küreseleşmiş dünyada, negatif diyalektik yaklaşımla, kamusal ve özelin sınırlarının belirsizleşmiş olması, kamusal alanı bireyin çağdaş dünyadaki gereksinimlerini anlamak ve kapitalist sistemin dayatmalarına karşı koymak için tartışmaya açan bir itici güçtür. Bu bağlamda kamusal mekan ve özel mekan arasında net ayırım yapılmakta, ve çeşitli kavramlar üretilmekte ve tanımlar yapılmaktadır, ancak bu tez kamusal ve özel alanın bireyin açık uçlu dönüşümü üzerinden tartışılması gerektiğini önermektedir. Kamusal alan, mimarlık pratiğine yeni bir açılım sağlamak amacıyla bireyin zamanmekansal deneyimi olarak yeniden tanımlanmıştır. Kamusal alan olgusunu anlamak için, bir tür zamanmekansal deneyim modeli, kamuzel yeri incelemek için önerilmiştir. İstiklal Caddesi’nin arkitektonikleri ve mekansal kurguları kamuzel yerdeki kamusal alanın zamanmekansal deneyimini anlamak için yorumlanmıştır. İstiklal Caddesi kullanıcıya/gözlemciye/algılayana kamusal alanı zamanmekansal deneyim olarak sunma gerilimlerine sahip çok katmanlı bir zaman-mekan olarak değerlendirilmiştir. Sonuç olarak kamusal alan olgusunu küreselleşmiş dünya içinden anlama gereği mimarlık pratiği için bir imkan olarak alınmış ve kamusal alan eleştirel bireyin kamuzel yerdeki zamanmekansal deneyimi olarak yeniden tanımlanmıştır.

In the globalized world, where the powers of capitalism threatening the public sphere and private sphere of the individuals, but at the same time, in a negative dialectical approach, the indefiniteness of the borders of public and private sphere is an impulse for opening public sphere into discussion to understand the requirements of the critical individual in the contemporary world and counteract the impositions of capitalist system. In this regard various concepts are produced and definitions are made in order to draw a borderline between public space and private space; however the research proposes that the public and private should be discussed as an open-ended transformation of the individual in space-time. Public sphere is re-defined as spatiotemporal experience of the critical individual, in order to provide an opening to architectural praxis. A kind of spatiotemporal experiencing model for analysing inbetween public-private place in order to understand public sphere phenomenon is suggested. The architectonics and spatial configurations of İstiklal Avenue is interpreted in order to understand the spatiotemporal experience of public sphere in in-between public-private place. İstiklal Avenue is evaluated as a multi-layered space-time, which has potentials to offer public sphere as spatiotemporal experience to its user/viewer/perceiver/observers. In conclusion, the need for understanding the phenomenon of public sphere in the globalized world is taken as an opportunity for architectural praxis, and public sphere is re-defined as spatiotemporal experience of the critical individual in in-between publicprivate places.
Public Sphere As Spatiotemporal Experience
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2009
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2009
Keywords: Kamusal alan; Zamanmekansal deneyim; Kamuzel; Eleştirel birey; Public sphere; Spatiotemporal experience; In-between public-private